Animação estereoscópica: relações entre a tecnologia audiovisual e a percepção da profundidade - Santos, Tiago Eugenio dos (Universidade Federal de São Carlos, 2014)
The stereoscopic application is not in itself a technical novelty, because, already in 1838, the first device that allowed the stereoscopic display is designed. In the early years of its invention new apparatus were constructed in an attempt to combine animation with stereoscopy. The 1910s and 1920s are marked by the beginning of the use of stereoscopy in the cinema and at the end of the 1930s in film animation. Since then, there have been periods of great productivity alternated by periods of relative calm. Today, we live in a time in which stereoscopy comes back to matter in the film scene, especially in animated films. This research builds a historical overview of stereoscopy, stereoscopic cinema and stereoscopic animated film. It also exposes the particularities of a stereoscopic audiovisual piece and discusses the specifics of the application of stereoscopy in animated films. Using as reference periods of stereoscopic film according to the author Ray Zone, this research aims to analyze the use of stereoscopy in animations from different historical periods. The selected works for the analysis are: Motor Rhythm (1952), Starchaser: The Legend of Orin (1985) and Brave (2012). In order to verify the implementation of stereoscopy and the role of parallax in the pieces chosen, an analysis methodology was developed so that we could be able to determine the application of stereoscopy within an audiovisual work while also addressing its narrative composition.
Keywords: Cinema; Estereoscopia; Animação; Tecnologia audiovisual; Narrativas; Estereoscopy; Cinema; Animation; Audiovisual technology; Narrative language; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA